2020
DOI: 10.1111/1346-8138.15709
|View full text |Cite
|
Sign up to set email alerts
|

Early add‐on administration of mepolizumab and intravenous immunoglobulin effective in treating eosinophilic granulomatosis with polyangiitis

Abstract: Treatment of eosinophilic granulomatosis with polyangiitis (EGPA) remains a challenge because currently available therapies, corticosteroids and immunomodulators, do not always control symptoms and are often associated with significant morbidity and relapse. Mepolizumab has been demonstrated to be an effective add-on therapy with steroid-sparing effect in cases of relapsing or refractory EGPA. Intravenous immunoglobulin (IVIG) therapy is effective against mononeuritis multiplex or heart failure in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…We have previously reported the safety and effectiveness of MPZ in maintenance therapy in relapsing and refractory EGPA in clinical settings [7]. MPZ is an effective agent for maintenance therapy; moreover, since MPZ has been used as remission induction therapy for steroid-resistant EGPA, it has started to attract increased attention [8][9][10][11]. In the present study, we assessed the safety and effectiveness of MPZ at a dose of 300 mg/ month in combination with high-dose CS as remission induction therapy for EGPA in real-world clinical settings.…”
mentioning
confidence: 99%
“…We have previously reported the safety and effectiveness of MPZ in maintenance therapy in relapsing and refractory EGPA in clinical settings [7]. MPZ is an effective agent for maintenance therapy; moreover, since MPZ has been used as remission induction therapy for steroid-resistant EGPA, it has started to attract increased attention [8][9][10][11]. In the present study, we assessed the safety and effectiveness of MPZ at a dose of 300 mg/ month in combination with high-dose CS as remission induction therapy for EGPA in real-world clinical settings.…”
mentioning
confidence: 99%
“…The high-dose IVIG might be effective for patients with heart failure or peripheral neuropathy not responsive to standard immunosuppressive therapy (40)(41)(42). A recent study suggested that earlier add-on combination administration of IVIG and mepolizumab might be efficient adjunct treatment to induce clinical remission and decrease relapse risk for patients with EGPA (43).…”
Section: Discussionmentioning
confidence: 99%
“…112 , 135 , 136 , 137 However, there are significant risks associated with long‐term use of OCS 138 ; therefore, early initiation of targeted biologic treatment is essential to reduce OCS use, 44 , 64 , 82 , 101 and achieve the best results for patients. This is especially true for patients with EGPA 139 or HES, 140 since serious, irreparable damage, and remodeling may develop during the disease course. 141 This is also true for patients with severe asthma, as eosinophil‐driven changes to the airways are associated with reduced lung function.…”
Section: Future Directionsmentioning
confidence: 99%